Quantitatively determining the degree of spin fluctuations in actinide metals and compounds. (12th October 2020) - Liu, Yi; Ji, Xingyu; Pan, Qifa; Zhang, Yun; Wang, Xiaoying; Lai, Xinchun
Abstract: Actinide materials are well-documented for nuclear properties, but their 5f electrons that produce exotic phenomena are not, due to the complexity of a dual localized and itinerant nature that remains a mystery. Particular interest is given to the electronic correlations at the localized and itinerant boundary where strong spin fluctuations are present. We report the identification of an intensity defined by integrating the normalized resistivity that approximately provides a quantitative measure of spin fluctuations. The intensity is very sensitive to the tuning of non-thermal parameters such as pressure and chemical doping, probing the anomalies in the evolution of spin fluctuations close to a valence or magnetic instability. In this way, our results are not only connected with the long-standing controversy on the anomalous low-temperature resistivity behavior of actinide metals, but also highlight an unconventional type of superconducting pairing, mediated by valence and/or spin fluctuations, for a wealth of 4f and 5f-electron systems. In an unified picture proposed, it is helpful to determine the degree of spin fluctuations for understanding the origin of the emergent superconductivity in systems with correlated electrons.